Composite ceramic coating, preparation method and application
ZrN/MoS2 coating was prepared through collaboratively regulated magnetron sputtering technology, and the interlaced MoS2 and ZrN layers were used to solve the problem of easy oxidation and wear of the molybdenum disulfide coating in high temperature and high speed environments, achieving high hardness and low hardness Friction coefficient and enhanced wear resistance, suitable for large-scale production of ceramic coatings.
Patent Information
- Application Number
- CN202411525671.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-18
AI Technical Summary
The existing molybdenum disulfide (MoS2) coatings are prone to oxidation and wear rates under high temperature and high speed environments, and the high cost of ceramic coatings is not suitable for large-scale production.
By coordinating the nitrogen flux, power and substrate bias of DC/RF magnetron sputtering technology, ZrN/MoS2 coating was prepared, and the interlaced MoS2 soft coating and ZrN hard coating were used to achieve soft and hard coating. The materials cooperate to enhance wear resistance and durability.
The high hardness and low friction coefficient of ZrN/MoS2 coating are achieved, crack diffusion is suppressed, and the toughness and wear resistance of the material are significantly improved. It is suitable for mass production.
Smart Images

Figure CN119465049A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of coating preparation, and in particular to a composite ceramic coating, a preparation method and an application thereof. Background Art
[0002] In the context of serious energy problems in today's world, controlling friction and reducing wear are important means to improve the life of mechanical structures, the stability and reliability of component operation. Molybdenum disulfide (MoS2), as a typical solid lubricant, has excellent thermal stability, low shear strength and strong surface adhesion. It has been widely used in the lubrication of bearings, gears and other mechanical parts in the aerospace field. However, due to its easy oxidation in the atmospheric environment and low hardness, the MoS2 coating used in rolling bearings often fails due to complex effects such as friction and collision between rolling elements, cages and inner and outer raceways, such as peeling, wear and oxidation.
[0003] Existing ceramic coating preparation technology, such as a gradient diamond / molybdenum disulfide composite self-lubricating and anti-friction engineering ceramic coating and its preparation method provided by publication number CN118561623A, wherein the coating is a multi-level size progressive diamond coating and a molybdenum disulfide coating from the surface of the engineering ceramic substrate outward; each level of the size progressive diamond coating includes a micron diamond coating, a fine-grained diamond coating and a nano diamond coating, and a molybdenum disulfide coating is deposited on the diamond coating; the deposited diamond coating is prepared by hot wire chemical vapor deposition, and the molybdenum disulfide film covering the diamond coating is prepared by DC magnetron sputtering; but since the application uses diamond material to prepare the ceramic coating, its cost is relatively high and it is not suitable for mass production of ceramic coatings.
[0004] In addition, in the prior art, adhesives and other additives are added to molybdenum disulfide (MoS2) powder to make it into anti-friction rubber. The mechanism of action of the anti-friction rubber is to use surface adhesive coating technology to achieve friction reduction, wear repair and pre-protection by means of a solidified coating of rubber on the friction surface through physical and chemical reactions. For example, Zhang Weihong added epoxy resin as adhesive to molybdenum disulfide (MoS2), used low molecular weight polyamide resin as curing agent, and added auxiliary materials such as graphite and aluminum oxide to make anti-friction rubber. The molybdenum disulfide (MoS2) anti-friction rubber thus made has the advantages of long service life and wide applicable working conditions, but wear is still obvious under high-speed friction conditions.
[0005] In recent years, most of the sputtering deposition of molybdenum disulfide (MoS2) has been done by improving the performance of lubricating films through metal dopants and composite film bottom composite sputtering. Although the sputtering deposition coating method of molybdenum disulfide (MoS2) has great advantages in both technology and industrial-scale production, it cannot solve the problems of easy oxidation and high wear rate under high temperature and high speed. The thermal spraying method has the characteristics of diversity, wide range of coating preparation and economic application, but the structure of the general coating is uneven, and there will be contamination inclusions in the interval between spraying, resulting in a layered structure, resulting in weak bonding force; the thermal diffusion method is easy to operate and can obtain a thicker lubricating coating, but it cannot currently increase the hardness by metal doping, and there are few reports on the optimal film-forming parameters, which temporarily cannot be applied in practice. In summary, only by adopting the molybdenum disulfide (MoS2) coating technology that conforms to the specific working conditions can the ideal effect be achieved. It is worth noting that the method of alternating magnetron sputtering and sputtering can improve the bonding strength of the film. The coating technology combining ion beam enhanced deposition and ion beam sputtering deposition not only has higher bonding strength and better density than pure sputtering film, but also improves the durability of the film. Summary of the invention
[0006] In view of the above-mentioned problems, the present invention aims to provide a composite ceramic coating, a preparation method and an application thereof. By synergistically regulating the nitrogen flux, power and substrate bias of DC / RF magnetron sputtering technology, a ZrN / MoS2 coating with both high hardness and low friction coefficient is prepared. The composite ceramic coating has the characteristics of soft and hard substances alternating. The tensile load is borne by the staggered MoS2 soft coating, and the load transfer between the hard coatings is achieved through the shear deformation of the ZrN hard coating. The introduction of interfaces in the staggered arrangement restrains the formation of cracks and inhibits the diffusion of cracks during wear. The soft and hard substances cooperate with each other to achieve toughening and wear resistance, thereby further improving the overall performance of the material.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A composite ceramic coating comprises a ZrN / MoS2 coating, wherein the ZrN / MoS2 coating is formed by alternately depositing multiple ZrN layers and MoS2 layers.
[0009] The single layer thickness of the ZrN layer is 0.05-0.1 μm, and the single layer thickness ratio of the ZrN layer to the MoS2 layer is 1:1, that is, the single layer thickness of the MoS2 layer is 0.05-0.1 μm. When multiple ZrN layers and MoS2 layers are alternately deposited, the total thickness of the formed ZrN / MoS2 coating is 1 μm.
[0010] A method for preparing a composite ceramic coating comprises the following steps:
[0011] S1. Select a stainless steel substrate, polish and clean the surface of the substrate, and perform glow cleaning on the substrate to activate the surface of the substrate;
[0012] S2. In a deposition device with an argon flux of 80 sccm, a base layer is prepared by coordinated regulation of DC / RF magnetron sputtering technology, a DC power of 150 W is applied to the Zr target, the bias condition is -25 V, the Zr target is turned on, the distance between the substrate and the target surface of the Zr target is 100 mm, the internal air pressure of the deposition device is 0.5 Pa, the substrate rotation speed is maintained at 10 r / min, and a Zr base layer with a thickness of 0.1 μm to 0.2 μm is deposited on the activated substrate;
[0013] S3, adjusting the argon gas flux in the deposition equipment to 80 sccm, and introducing nitrogen gas with a flux of 9 sccm into the interior thereof, adjusting the AC power applied to the Zr target to 150 W, the bias condition to -25 V, depositing a 0.05 μm to 0.1 μm ZrN layer on the Zr base layer, and closing the Zr target;
[0014] Apply radio frequency power to the MoS2 target, the power of the radio frequency power is 110W, the bias condition is 0V, turn on the MoS2 target, deposit a MoS2 layer of 0.05μm to 0.1μm on the ZrN layer, and turn off the MoS2 target;
[0015] S4. Repeat S3 to alternately deposit ZrN layers and MoS2 layers until a ZrN / MoS2 coating with a total thickness of 1 μm is obtained.
[0016] An application of a composite ceramic coating, wherein the composite ceramic coating is used for coating on a bearing surface.
[0017] The beneficial effects of the present invention are:
[0018] 1. The present invention prepares a composite ceramic coating for coating on the bearing surface by synergistically regulating the nitrogen flux, power and substrate bias of DC / RF magnetron sputtering technology. During the preparation process, the production of harmful substances can be avoided, which is beneficial to environmental protection.
[0019] 2. The composite ceramic coating prepared by the present invention bears the tensile load through the staggered MoS2 soft coating, and realizes the load transfer between the hard coatings through the shear deformation of the ZrN hard coating, which can restrain the cracks and inhibit the diffusion of cracks during the wear process. The soft and hard materials cooperate with each other to achieve the toughening and wear resistance effect, further improving the overall performance of the material.
[0020] 3. The preparation method of the present invention has a simple process and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a comparison chart of hardness and elastic modulus performance between the embodiments of the present invention and the comparative examples;
[0022] Figure 2 This is a comparison chart of friction coefficient performance between the embodiments of the present invention and the comparative examples;
[0023] Figure 3 A comparison chart of wear rate performance between the embodiments of the present invention and the comparative examples;
[0024] Figure 4 This is a comparison diagram of the indentation cracks produced after testing of samples prepared in the embodiments of the present invention and the comparative examples. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The components of the embodiments of the present application described and shown in the drawings here can be arranged and designed in various different configurations.
[0026] The inventors have found that molybdenum disulfide (MoS2), as a typical solid lubricating material, has excellent thermal stability, low shear strength and strong surface adhesion, and has been widely used in the lubrication of mechanical parts such as bearings and gears in the aerospace field. However, due to its easy oxidation in the atmospheric environment and low hardness, the MoS2 coating used in rolling bearings often fails due to complex effects such as friction and collision between rolling elements, retaining cages and inner and outer raceways, such as peeling, wear and oxidation. The existing ceramic coating made in combination with MoS2 is not suitable for large-scale mass production due to its high material cost.
[0027] Based on the above findings, the present application proposes a composite ceramic coating. By synergistically regulating the nitrogen flux, power and substrate bias of DC / RF magnetron sputtering technology, a ZrN / MoS2 coating with both high hardness and low friction coefficient is prepared. The composite ceramic coating has the characteristics of soft and hard substances alternating. The tensile load is borne by the staggered MoS2 soft coating, and the load transfer between the hard coatings is achieved through the shear deformation of the ZrN (chromium nitride) hard coating. The introduction of the interface in the staggered arrangement restrains the formation of cracks and inhibits the diffusion of cracks during wear. The soft and hard substances cooperate with each other to achieve toughening and wear resistance, thereby further improving the overall performance of the material.
[0028] Example 1
[0029] A composite ceramic coating comprises a ZrN / MoS2 coating, wherein the ZrN / MoS2 coating is formed by alternately depositing multiple ZrN layers and MoS2 layers.
[0030] The single layer thickness of the ZrN layer is 0.05 μm, and the single layer thickness ratio of the ZrN layer to the MoS2 layer is 1:1, that is, the single layer thickness of the MoS2 layer is 0.05 μm. When multiple ZrN layers and MoS2 layers are alternately deposited, the total thickness of the formed ZrN / MoS2 coating is 1 μm.
[0031] A method for preparing a composite ceramic coating comprises the following steps:
[0032] S1. Select a 316 stainless steel substrate of 5 cm × 5 cm × 0.2 cm, polish the surface of the substrate, place the polished substrate in an alcohol solution for ultrasonic cleaning for 20 minutes, and repeat the replacement of the alcohol solution and cleaning for 3 to 5 times;
[0033] The cleaned substrate is placed in an argon environment, 80 mm to 120 mm away from the target surface of the Zr target, and the substrate is rotated at 10 r / min. The argon flow rate is adjusted to 100 sccm, the vacuum degree is adjusted to 0.5 Pa, and the substrate is glow cleaned for 20 to 30 minutes under a bias condition of -100 V to -200 V to activate the substrate surface;
[0034] S2. In a deposition device with an argon flux of 80 sccm, a base layer is prepared by coordinated regulation of DC / RF magnetron sputtering technology, a DC power of 150 W is applied to the Zr target, the bias condition is -25 V, the Zr target is turned on, the distance between the substrate and the target surface of the Zr target is 100 mm, the internal air pressure of the deposition device is 0.5 Pa, the substrate rotation speed is maintained at 10 r / min, and a Zr base layer with a thickness of 0.1 μm to 0.2 μm is deposited on the activated substrate;
[0035] S3, adjusting the argon gas flux in the deposition equipment to 80 sccm, and introducing nitrogen gas with a flux of 9 sccm into the interior thereof, adjusting the AC power applied to the Zr target to 150 W, the bias condition to -25 V, depositing a 0.05 μm ZrN layer on the Zr base layer, and closing the Zr target;
[0036] Apply radio frequency power to the MoS2 target, the power of the radio frequency power is 110W, the bias condition is 0V, turn on the MoS2 target, deposit a 0.05μm MoS2 layer on the ZrN layer, and turn off the MoS2 target;
[0037] S4. Repeat S3 to alternately deposit ZrN layers and MoS2 layers, that is, repeat the alternate deposition for 10 cycles until a ZrN / MoS2 coating with a total thickness of 1 μm is obtained.
[0038] Example 2
[0039] A composite ceramic coating comprises a ZrN / MoS2 coating, wherein the ZrN / MoS2 coating is formed by alternately depositing multiple ZrN layers and MoS2 layers.
[0040] The single layer thickness of the ZrN layer is 0.1 μm, and the single layer thickness ratio of the ZrN layer to the MoS2 layer is 1:1, that is, the single layer thickness of the MoS2 layer is 0.1 μm. When multiple ZrN layers and MoS2 layers are alternately deposited, the total thickness of the ZrN / MoS2 coating formed is 1 μm.
[0041] The operation steps and parameter settings of S1 and S2 in Example 2 are the same as those in Example 1, except that:
[0042] In S3, the single layer thickness of the deposited ZrN layer is 0.1 μm, the single layer thickness of the deposited MoS2 layer is 0.1 μm, and the other parameters are set the same;
[0043] In S4, the ZrN layer and the MoS2 layer are alternately deposited for 5 cycles to obtain a ZrN / MoS2 coating with a total thickness of 1 μm.
[0044] Comparative Example 1
[0045] S1 and S2 in the comparative example are the same as those in Example 1, except that:
[0046] In Comparative Example 1, only a MoS2 coating with a thickness of 1 μm was deposited, and the other parameters were set the same.
[0047] The following is a comparison of the ZrN / MoS2 coating obtained in Example 1, the ZrN / MoS2 coating obtained in Example 2, and the MoS2 coating obtained in Comparative Example 1 in terms of hardness, elastic modulus, friction coefficient, and wear performance:
[0048] 1. Hardness / elastic modulus test:
[0049] In order to obtain the microscopic mechanical properties of the coatings obtained in the embodiments and comparative examples, including hardness and elastic modulus information, the coatings were tested using nanoindentation technology. This experiment used a nanoindenter produced by Keysight Technologies, Inc., USA, model G200, and a diamond Berkovichtip indenter with a curvature radius of 20 nm. Each sample obtained in the embodiments and comparative examples was tested 32 times at different positions, and the average value was taken as the hardness value and elastic modulus value of each sample.
[0050] The hardness / elastic modulus test results are as follows: Figure 1As shown, the horizontal axis lists the three test samples of Example 1, Example 2 and Comparative Example 1 respectively, the left vertical axis lists the hardness performance parameters of the test samples, which are represented by yellow columns in the figure, and the right horizontal axis lists the elastic modulus performance parameters of the test samples, which are represented by green columns in the figure. Figure 1 It can be seen that:
[0051] The hardness of the ZrN / MoS2 coating obtained in Example 1 is 8.5 Gp, and the elastic modulus is 110 GPa; the hardness of the ZrN / MoS2 coating obtained in Example 2 is 6.5 Gpa, and the elastic modulus is 90 GPa; the hardness of the MoS2 coating obtained in Comparative Example 1 is 3 GPa, and the elastic modulus is 65 GPa.
[0052] Combination Figure 1 From the information shown and the above experimental data, it can be concluded that, compared with the single-layer MoS2 coating provided in Comparative Example 1, the ZrN / MoS2 composite ceramic coating prepared by the preparation method provided by the present invention in Examples 1 and 2 has both high hardness and high elastic modulus, and has strong comprehensive performance, among which the sample obtained in Example 1 has the best performance.
[0053] 2. Friction coefficient test:
[0054] The friction coefficient performance of the coatings obtained in the embodiments and the comparative examples was tested using a ball-disc rotating friction and wear tester produced by Lanzhou Huahui Instrument Technology Co., Ltd. The tester model was MS-T3001, the friction pair used a ZrO2 ball with a diameter of 6 mm, the applied load was 100 g, the rotation speed was 200 r / min, and the test time was 30 min;
[0055] The friction coefficient test results are as follows: Figure 2 As shown in the figure, the horizontal axis represents the test time, and the vertical axis represents the friction coefficient performance parameters of each sample. Figure 2 In the figure, black, red and blue are used to represent the changes in the friction coefficient of the samples prepared in Example 1, Example 2 and Comparative Example 1 during the test. Figure 2 It can be seen that:
[0056] The average friction coefficient of the ZrN / MoS2 coating obtained in Example 1 is 0.0887; the average friction coefficient of the ZrN / MoS2 coating obtained in Example 2 is 0.2286; the average friction coefficient of the MoS2 coating obtained in Comparative Example 1 is 0.3892;
[0057] Combination Figure 2From the information shown and the above experimental data, it can be concluded that, compared with the single-layer MoS2 coating provided in Comparative Example 1, the ZrN / MoS2 coatings prepared by the preparation method provided by the present invention in Examples 1 and 2 both have a smaller friction coefficient, among which the sample performance obtained in Example 1 is the best. It can be seen that when the coating prepared by the method provided by the present invention is applied to the bearing, it can provide good protection for the bearing without affecting the performance of the bearing.
[0058] 3. Wear performance test:
[0059] In order to calculate the wear rate, a 3D optical profiler was used to characterize the morphology of the sample after wear. The equipment used in this test was produced by Aite Instrument Technology Co., Ltd., model UP-Lambda. The wear resistance of the coating was compared by the wear rate. The wear rate was calculated by the formula: wear rate = V / (L×F), where V is the wear scar volume, L is the total wear length, and F is the applied load during wear; the higher the wear rate, the worse the wear resistance of the coating;
[0060] Each sample prepared in Example 1, Example 2 and Comparative Example 1 was tested 3 times, and the average value was taken as the wear rate of each sample. The wear rate performance test results obtained are as follows: Figure 3 As shown, the horizontal axis lists the three test samples of Example 1, Example 2 and Comparative Example 1 respectively, and the vertical axis represents the wear rate performance parameters of the samples. The wear rate of each sample is represented by a gradient color block. Figure 3 It can be seen that:
[0061] The wear rate of Example 1 is 0.8292×10-6mm 3 / Nm, the wear rate of Example 2 is 2.0965×10-6mm 3 / Nm, the wear rate of comparative example 1 is 2.9578×10-6mm 3 / Nm;
[0062] Combination Figure 3 From the information and the above data, it can be seen that, compared with the single-layer MoS2 coating provided in Comparative Example 1, the ZrN / MoS2 coating prepared by the method provided by the present invention in Examples 1 and 2 can effectively improve the wear resistance of the substrate, wherein the wear rate of Example 1 is much lower than that of the comparative example. It can be concluded that when the ZrN / MoS2 coating prepared by the method provided by the present invention is applied to the bearing surface, it has stronger wear resistance;
[0063] It can be seen from all the above test results that the ZrN / MoS2 coating prepared by the method provided by the present invention and with the parameters adopted in Example 1 has the best performance.
[0064] See also Figure 4 ,like Figure 4 Shown are coating samples prepared by Example 1 of the present invention and Comparative Example 1, and a comparison diagram of indentation cracks obtained by observing under a microscope after testing. It can be seen from the figure that the sample prepared in Example 1 only produced a few cracks at the edge after the test, while the sample prepared in Comparative Example 1 produced multiple cracks on the surface. Through comparison, it can be concluded that the composite ceramic coating prepared by the method provided by the present invention can withstand tensile loads through the staggered MoS2 soft coatings, and realize load transfer between hard coatings through the shear deformation of the ZrN hard coatings. In the process of applying to the bearing surface for use, it can have a certain restraining effect on the formation of cracks, inhibit the spread of cracks during wear, and achieve toughening and wear resistance through the synergistic cooperation of soft and hard substances, which can further improve the overall performance of the material.
Claims
1. A composite ceramic coating, characterized in that: The composite ceramic coating is a ZrN / MoS2 coating formed by alternately depositing multiple ZrN layers and MoS2 layers.
2. A composite ceramic coating according to claim 1, characterized in that: The single layer thickness of the ZrN layer is 0.05 μm to 0.1 μm, and the single layer thickness ratio of the ZrN layer to the MoS2 layer is 1:
1.
3. A composite ceramic coating according to claim 1, characterized in that: The total thickness of the ZrN / MoS2 coating is 1 μm.
4. A method for preparing a composite ceramic coating according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Select a stainless steel substrate, polish and clean the surface of the substrate, and perform glow cleaning on the substrate to activate the surface of the substrate; S2. In a deposition device under an argon environment, a base layer is prepared by coordinated regulation of a DC / RF magnetron sputtering technique, a DC power is applied to a Zr target, the Zr target is turned on, and a Zr base layer is deposited on the activated substrate; S3, nitrogen is introduced into the argon environment, a ZrN layer of a certain thickness is deposited on the Zr base layer, and the Zr target is turned off; radio frequency power is applied to the MoS2 target, the MoS2 target is turned on, a MoS2 layer of a certain thickness is deposited on the ZrN layer, and the MoS2 target is turned off; S4. Repeat S3 to alternately deposit ZrN layers and MoS2 layers until a ZrN / MoS2 coating with a total thickness of 1 μm is obtained.
5. The method for preparing a composite ceramic coating according to claim 4, characterized in that: The parameters in S2 are: the argon gas flux is 80 sccm, the DC power applied to the Zr target is 150 W, the bias condition is -25 V, and the substrate rotation speed is 10 r / min.
6. The method for preparing a composite ceramic coating according to claim 4, characterized in that: In S3, the parameters for depositing the ZrN layer are: an argon flux of 80 sccm, a nitrogen flux of 9 sscm, a DC power of 150 W applied to the Zr target, a bias condition of -25 V, and a substrate rotation speed of 10 r / min.
7. The method for preparing a composite ceramic coating according to claim 4, characterized in that: In S3, the parameters for depositing the MoS2 layer are: the RF power applied to the MoS2 target is 110 W, the bias condition is 0 V, and the substrate rotation speed is 10 r / min.
8. The method for preparing a composite ceramic coating according to claim 4, characterized in that: In S2 and S3, the distance between the substrate and the target surface of the Zr target or the MoS2 target is 100 mm, and the internal gas pressure of the deposition equipment is 0.5 Pa.
9. The method for preparing a composite ceramic coating according to claim 4, characterized in that: The thickness of the Zr base layer deposited in the S2 is 0.1 μm to 0.2 μm.
10. Application of a composite ceramic coating according to any one of claims 1 to 3, characterized in that: The composite ceramic coating is used for coating on the bearing surface.
Citation Information
Patent Citations
Gradient diamond / molybdenum disulfide composite self-lubricating anti-attrition engineering ceramic coating and preparation method thereof
CN118561623A